The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nano12101676
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials in Dentistry: Current Applications and Future Scope

Abstract: Nanotechnology utilizes the mechanics to control the size and morphology of the particles in the required nano range for accomplishing the intended purposes. There was a time when it was predominantly applied only to the fields of matter physics or chemical engineering, but with time, biological scientists recognized its vast benefits and explored the advantages in their respective fields. This extension of nanotechnology in the field of dentistry is termed ‘Nanodentistry.’ It is revolutionizing every aspect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 157 publications
1
13
0
Order By: Relevance
“…Prior studies reported that the release of fluoride from glass ionomer cement follows an exponential pattern rather than a linear pattern, with the maximum amount of release occurring in the first and second days of its restoration in the oral cavity, which significantly decreases until it reaches the lowest amount on day 30 [24,[38][39][40]. A similar observation was evident in the present study and the difference was considerably not high.…”
Section: Discussionsupporting
confidence: 86%
“…Prior studies reported that the release of fluoride from glass ionomer cement follows an exponential pattern rather than a linear pattern, with the maximum amount of release occurring in the first and second days of its restoration in the oral cavity, which significantly decreases until it reaches the lowest amount on day 30 [24,[38][39][40]. A similar observation was evident in the present study and the difference was considerably not high.…”
Section: Discussionsupporting
confidence: 86%
“…Metaloxide nanoparticles (TiO 2 , ZnO, Ag_TiO 2 , N_TiO 2 and NF_TiO 2 ) have gained the attention of researchers due to their ability to generate reactive oxygen species (ROS) and their proven strong antimicrobial and biomimetic effects [ 52 ]. Nanoparticles have been utilized in orthodontics, prosthodontics, and restorative dentistry with the objective to improve materials’ mechanical properties and reduce the microbial load adjacent or attached to different types of restorations [ 53 ]. Previous studies confirmed that the incorporation of metaloxide nanoparticles into dental polymers resulted in experimental materials with improved physical, mechanical, biological, and biocompatibility properties, thereby supporting the continued development and characterization of nanofilled materials [ 29 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature reviews disclose that preventive dentistry, restorative dentistry, endodontics, implantology, prosthetic dentistry, oral cancers, and periodontology all benefit from NPs ( Fig. 1 ) [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission from Ref. [ 38 ], with the permission of the Creative Commons Attribution 4.0 International License ( http://creativecommons.org/licenses/by/4.0/ ). Copyright 2022, MDPI.…”
Section: Introductionmentioning
confidence: 99%